Assessment of Land Capability and Zoning for Sustainable Urban Development in Ambon City - Lasaiba, Mohammad Amin (Jurnal Geospasial Indonesia, 2024)
The optimization strategy replaces ability-useful land with conservation-source power land, which may help with problem degradation. Investigate this to determine the level of land ability and the function area designation for good protection and cultivation in the Satuan Wilayah Pengembangan (SWP). The research method is descriptive and quantitative, with stepwise data collection and processing. Data collection is carried out through studies and literature from several agencies. Temporary spatial data analysis was conducted using Geographic Information System (GIS) software. The research findings underscore a significant aspect regarding land analysis, specifically about allocating areas for settlement purposes. The documented 3687.35 hectares identified as suitable for settlement development, alongside the approximately 11755.27 hectares allocated as buffer zones, highlight a limited portion of land deemed suitable for urban expansion within the studied region. This observation underscores the challenge of finding suitable and adequate spaces for urban development initiatives in Ambon City. Identifying such a confined area underscores the need for strategic urban planning that considers land constraints, such as the predominantly hilly terrain, to ensure balanced development, efficient land use, and the preservation of environmental integrity. Efforts toward optimizing these available areas for urban growth while concurrently focusing on conservation and ecological sustainability become imperative for Ambon City's future urban development trajectory. They created a barrier to physical land where hilly areas dominate the characteristics of the Ambon City area